A delay-constrained energy-efficient component carrier adjusting scheme for LTE-Advanced systems - 陈华夏 Hu Honglin (高技术通讯（英文版）, 2014)
The energy efficiency and packet delay tradeoffs in long term evolution-advanced （LTE-A） systems are investigated.Analytical expressions are derived to explain the relation of energy efficiency to mean packet delay,arrival rate and component carrier （CC） configurations,from the theoretical respective which reveals that the energy efficiency of multiple CC systems is closely related to the frequency of CCs and the number of active CCs.Based on the theoretical analysis,a CC adjusting scheme for LTE-A systems is proposed to maximize energy efficiency subject to delay constraint by dynamically altering the on/off state of CCs according to traffic variations.Numerical and simulation results show that for CCs in different frequency bands with equal transmit power,the proposed scheme could significantly improve the energy efficiency of users in all aggregation levels within the constraint of mean packet delay.